Personal data management and accountability: European regulation, market principles and civic agency strategies. Issue 3 (27th May 2019) - Yauri Miranda, Jaseff Raziel
ABSTRACT: Digital personal data could be used in different ways to administrate populations, as in the case of commercial exploitation and surveillance to regulate individuals' preferences and behavior. In that sense, this article questions whether accountability can transform this kind of usage in two fronts: (a) to guarantee a certain degree of privacy and individual autonomy, and, (b) to replenish the asymmetries of power between personal data subjects and data processors. In order to do so, we analyze the accountability of personal data in three domains at European Level: state-rooted regulations, market principles, and civic agency strategies. The conclusion explores new forms to redefine the use of personal data through the production, consumption, and control of this information, analyzing the limits and potentials of accountability in each domain.